Validity Of Notary Deeds And Land Deed Officials Made Electronically - Bagaskara Aji, Ilham; Suwandi, Pujiyono; Hadi, Hernawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study discusses Government Regulation Number 81 of 2021 which allows deeds to be made electronically which is linked to related laws and regulations in order to review whether electronic deeds are included in authentic deeds or not. This study aims to determine the legal basis for electronic deeds as authentic deeds and to determine the legal problems that will arise if notaries and PPATs make deeds electronically. This type of research is doctrinal normative research with a statutory approach using progressive legal theory. The findings of this study are that electronic deeds with the development of an advanced era like this can become authentic deeds with the note that there must be several regulations that must be changed to recognize electronic deeds as authentic deeds. The conclusion of this study is that electronic deeds produced by an Electronic Information system that has been legalized or guaranteed by authorized professionals in this case a notary and a land deed official are authentic deeds and there are still problems if electronic deeds are implemented, namely: Inconsistency with laws and regulations, There is no definite recognition of electronic deeds as authentic deeds, Validity and authenticity of electronic deeds, No digital evidence and forensics, Lack of infrastructure and readiness of implementers, No implementation guidelines.